Elucidating the role of growth rate on the production of a fusion protein under regulation of the hp4d promoter by Yarrowia lipolytica - Govender, Seshni (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.